2019
DOI: 10.1038/s41598-019-43148-z
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 inhibits the hepatocellular carcinoma progression by targeting long non-coding RNA UCA1

Abstract: Hepatocellular carcinoma (HCC) is one of the major causes of cancer-related death worldwide. However, the molecular mechanism underlying HCC carcinogenesis remains to be further elucidated. Up-frameshift protein 1 (UPF1) is a RNA/DNA-dependent ATPase and ATP-dependent RNA helicase. Here, we explored the expression and function of UPF1 in HCC. In this study, we demonstrated that UPF1 expression was significantly reduced in hepatocellular carcinoma (HCC) tissues compared with the adjacent normal tissues. And fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…The regulatory ncRNAs are broadly subcategorized into microRNAs (miRNAs, 18-25 nt), small interfering RNAs (siRNAs, <200 nt), piwi-interacting RNAs (piRNAs, <200 nt), and long noncoding RNAs (lncRNAs, >200 nt) [11]. Emerging studies on regulatory ncRNAs have shown their role as biomarkers or physiological regulators in many types of cancers, such as breast cancer, osteosarcoma, lung cancer, hepatocellular carcinoma, cervical cancer, bladder cancer [12][13][14][15][16]. Moreover, there have been increased investigations into the role of ncRNAs in ESCC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory ncRNAs are broadly subcategorized into microRNAs (miRNAs, 18-25 nt), small interfering RNAs (siRNAs, <200 nt), piwi-interacting RNAs (piRNAs, <200 nt), and long noncoding RNAs (lncRNAs, >200 nt) [11]. Emerging studies on regulatory ncRNAs have shown their role as biomarkers or physiological regulators in many types of cancers, such as breast cancer, osteosarcoma, lung cancer, hepatocellular carcinoma, cervical cancer, bladder cancer [12][13][14][15][16]. Moreover, there have been increased investigations into the role of ncRNAs in ESCC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Feng Q et al reported that UPF1 acted as an E3 ubiquitin ligase to repress human skeletal muscle differentiation [29]. In addition, UPF1 is proved to dysregulate in multiple tumors and in uence carcinogenesis [13][14][15]. However, there is lack of detailed study of UPF1 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…UPF1 is commonly mutated in pancreatic adenosquamous carcinoma (ASC) and there is little or no UPF1 expression in many ASC tumors compared to adjacent normal tissue [13]. It is revealed that UPF1 is downregulated in hepatocellular carcinoma and inhibits the tumor progression [14,15]. However, the role of UPF1 in oxaliplatin resistance in CRC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…UPF1 binds to MALAT1 and promotes its degradation, thereby inhibiting the expression of MALAT1 in gastric cancer ( Li et al, 2017 ). In HCC, the expression of UPF1 is decreased, and silencing of UPF1 promotes the growth and invasion of HCC cells ( Zhou et al, 2019 ). Knockdown of UPF1 in HCC cells increases the expression of UCA1 ( Zhou et al, 2019 ).…”
Section: Mechanisms Of Lncrna Interactions With Upf1mentioning
confidence: 99%